Nations of nothing but poetry modernism, transnationalism, and synthetic vernacular writing - Hart, Matthew, Ph.D. (New York ; Oxford : Oxford University Press, 2010)
What happens when poets combine vernacular language with the spirit of modernity? Can a poem be cosmopolitanism and vernacular at the same time? This book answers these questions through case studies of Scottish, English, and 'Black Atlantic' poetries from the landmark modernist year of 1922 through the mid 1970s.
Description based on print version record.
Includes bibliographical references and index.
Keywords: English poetry -- 20th century -- History and criticism; American poetry -- 20th century -- History and criticism; Poetry, Modern -- 20th century -- History and criticism; Modernism (Literature) -- English-speaking countries; Postcolonialism in literature; Transnationalism in literature